Fibroblast growth factor induced Ucp1 expression in preadipocytes requires PGE2 biosynthesis and glycolytic flux. Issue 5 (7th April 2021) - Gantert, Thomas; Henkel, Fiona; Wurmser, Christine; Oeckl, Josef; Fischer, Lena; Haid, Mark; Adamski, Jerzy; Esser‐von Bieren, Julia; Klingenspor, Martin; Fromme, Tobias
Abstract: High uncoupling protein 1 ( Ucp1 ) expression is a characteristic of differentiated brown adipocytes and is linked to adipogenic differentiation. Paracrine fibroblast growth factor 8b (FGF8b) strongly induces Ucp1 transcription in white adipocytes independent of adipogenesis. Here, we report that FGF8b and other paracrine FGFs act on brown and white preadipocytes to upregulate Ucp1 expression via a FGFR1‐MEK1/2‐ERK1/2 axis, independent of adipogenesis. Transcriptomic analysis revealed an upregulation of prostaglandin biosynthesis and glycolysis upon Fgf8b treatment of preadipocytes. Oxylipin measurement by LC‐MS/MS in FGF8b conditioned media identified prostaglandin E2 as a putative mediator of FGF8b induced Ucp1 transcription. RNA interference and pharmacological inhibition of the prostaglandin E2 biosynthetic pathway confirmed that PGE2 is causally involved in the control over Ucp1 transcription. Importantly, impairment of or failure to induce glycolytic flux blunted the induction of Ucp1, even in the presence of PGE2 . Lastly, a screening of transcription factors identified Nrf1 and Hes1 as required regulators of FGF8b induced Ucp1 expression. Thus, we conclude that paracrine FGFs co‐regulate prostaglandin and glucose metabolism to induce Ucp1 expression in a Nrf1 / Hes1 ‐dependent manner in preadipocytes, revealing a novel regulatory network in control of Ucp1 expression in a formerly unrecognized cell type.